Isolation, Characterization and Transcriptome Analysis of a Cytokinin Receptor Mutant Osckt1 in Rice - Ding, Wona; Tong, Huishan; Zheng, Wenjuan; Ye, Jing; Pan, Zhichong; Zhang, Botao; Zhu, Shihua (Frontiers in Plant Science, 2017)
Cytokinins play important roles in regulating plant development, including shoot and root meristems, leaf longevity, and grain yield. However, the in planta functions of rice cytokinin receptors have not been genetically characterized yet. Here we isolated a rice mutant, Osckt1, with enhanced tolerance to cytokinin treatment. Further analysis showed that Osckt1 was insensitive to aromatic cytokinins but responded normally to isoprenoid and phenylurea-type cytokinins. Map-based cloning revealed that the mutation occurred in a putative cytokinin receptor gene, histidine kinase 6 (OsHK6). OsCKT1 was found to be expressed in various tissues throughout the plant and the protein was located in the endoplasmic reticulum. In addition, whole-genome gene expression profiling analysis showed that OsCKT1 was involved in cytokinin regulation of a number of biological processes, including secondary metabolism, sucrose and starch metabolism, chlorophyll synthesis, and photosynthesis. Our results demonstrate that OsCKT1 plays important roles in cytokinin perception and control of root development in rice.